Subclinical Left Ventricular Dysfunction in Children and Adolescence With Thalassemia Intermedia - Isa Tafreshi, Roya; Radgoodarzi, Mohammad; Arjmandi Rafsanjani, Kadijeh; Soheilipour, Fahimeh (Frontiers in Pediatrics, 2022)
Background. Cardiac complications are important causes of morbidity in patients with thalassemia intermedia (TI). We aimed to assess left ventricular (LV) function, using new tissue Doppler imaging (TDI) indices, in order to diagnose early ventricular impairment in asymptomatic children and adolescence with the TI. Methods: We investigated possible differences in echocardiographic systolic and diastolic parameters between a population of 28 asymptomatic patients (mean age, 13.6 ±5.7 years) and 35 age-matched healthy control members. All of them underwent 2-D, pulsed Doppler, and tissue Doppler echocardiographic study for assessment of the LV mass, Trans-mitral velocities, mitral annular systolic and diastolic velocities, Myocardial performance index (MPI), and myocardial acceleration during isovolumic contraction (IVA). The cardiac iron load was estimated by magnetic resonance imaging T2*. Results: Left ventricular hypertrophy (LVH) was found in 13 (46.4%) patients. We found significantly reduced TDI- derived peak systolic myocardial velocity (s´) in patients, whereas no significant difference was identified between the patients and control group members when the IVA was compared. The ratio of peak mitral inflow velocity to annular early diastolic velocity (E/e´) of the mitral valve as an index of diastolic function was significantly higher in patients (9± 1 vs. 6± 1, p <0.05). Choosing a TDI derived MPI > 0.33 as a cut point, the global LV dysfunction was detected with a sensitivity of 78% and specificity of 80%. The patients with LVH significantly exhibited higher values of TDI-MPI, lower values of s´ velocity and IVA when compared against the subjects with normal LV mass. Conclusions: Subtle LV systolic and diastolic dysfunction develop early in young patients with the TI who have normal cardiac iron concentration. Moreover, LV remodeling as a main cardiac adaptive response plays a principal role in developing myocardial impairment.